Character formation in online education : a guide for instructors, administrators, and accrediting agencies - Jung, Joanne J. (Grand Rapids : Zondervan, 2015)
"Handy and practical, this user friendly book provides concrete tips and tools for growing learning communities in online courses that are marked by character growth in students--the kind of growth that is central to the mission of Christian higher education." -- Back Cover
Part one : rising to the challenge -- Log on to learn : inspiring students through an online course -- Charting a course : basics to developing an online course -- Partnerships that deliver : tag-teaming with a course designer -- Part two : elements of online character formation -- Taking online classroom technology to greater depths : the heart and community -- Conversation friendly : collaborative learning tools -- Premium blend : the hybrid course -- But I teach math! integrating faith and learning -- Social media : forming character with 140 characters -- Part three : building better outcomes -- Assessment : it's about stewardship.
Includes bibliographical references (page 139-142).
Keywords: Web-based instruction; Distance education; Personality development